2014
DOI: 10.1002/jsfa.6883
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality and the histological structure of breast and leg muscles in Ayam Cemani chickens, Ayam Cemani × Sussex hybrids and slow‐growing Hubbard JA 957 chickens

Abstract: Meat from Ayam Cemani chickens is a rich source of protein and could be highly valued by gourmet consumers, connoisseurs and dieticians for its rarity and originality. The results of this study show that genotype (Ayam Cemani, Ayam Cemani × Sussex, Hubbard JA 957) affected the quality and color of meat and the histological profile of chicken breast and leg muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
2
12
0
3
Order By: Relevance
“…In relation to the tenderness of meat, it is important to monitor muscle fibre characteristics. In accordance with the present study, Lukasiewicz et al [42] consistently reported that muscle fibre size is influenced by genotype. The total number of fibres was 15%-20% higher in the cockerels of the fast-growing line than in those of the slow-growing line [43].…”
Section: Discussionsupporting
confidence: 93%
“…In relation to the tenderness of meat, it is important to monitor muscle fibre characteristics. In accordance with the present study, Lukasiewicz et al [42] consistently reported that muscle fibre size is influenced by genotype. The total number of fibres was 15%-20% higher in the cockerels of the fast-growing line than in those of the slow-growing line [43].…”
Section: Discussionsupporting
confidence: 93%
“…Toughness is associated with dark, firm and dry meat, found especially in animals that are starved for too long. 49,50 The collagen content and the stability of cross-bridges increases as the animal ages, causing reduced tenderness. 46 This finding was also reported by Koohmaraie and Geesink 43 who observed that proteins such as nebulin and desmin play a role in the post-mortem tenderisation of meat as they lie next to the z-line.…”
Section: Resultsmentioning
confidence: 99%
“…46 This finding was also reported by Koohmaraie and Geesink 43 who observed that proteins such as nebulin and desmin play a role in the post-mortem tenderisation of meat as they lie next to the z-line. A study conducted in chicken by Łukasiewicz et al 49 indicated that genotype had an influence on the histological structure of muscles, such that tenderness, moisture content and muscle pH were affected. Tougher meat was associated with lean and older animals, and especially those that were stressed in the pre-slaughter environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of its plumage and body color, as well as its number of toes, this unique chicken breed resembles the indigenous Indonesian chicken breed Ayam cemani [2][3][4]. YO also has some morphological features that are similar to those of the Silkie fowl (called Ogolgye in Korea), except for a veiled black walnut comb and hair-like, fluffy plumage that is white or variably colored [5,6]. Although the exact origin of the YO breed has not yet been clearly defined, its features and medicinal usages were recorded in Dongui Bogam [7], a traditional Korean medical encyclopedia compiled and edited by Heo Jun in 1613.…”
Section: Introductionmentioning
confidence: 96%